Spatial Analysis of Surface Aquifer Thickness Based Frequency predominant in Bantul District - Nugroho Budi Wibowo (Department of Physics, Sebelas Maret University, 2015)
This research was conducted in Bantul in order to know the characteristics of the aquifer thickness on the top layer based on the predominant frequency value. This research was conducted by using 192 microtremor data and 32 bore hole data. The results showed that the thickness of the aquifer is more than 50 meters are in Jetis, Pundong and Bantul. Aquifer thickness> 50 m dominant in areas with predominant frequency interval (fo) 0.5 - 5 Hz contained in the district of Bantul, Bambanglipuro, Jetis and Pundong.